Cotton dyeing wastewater characteristics and its treatment efficiency using coconut shell activated carbon and limestone powder - Kamaruddin M.A.; Yusoff M.S.; Zawawi M.H. (University of Kuwait, 2023)
Textile wastewater often contains a mix of chemicals, solvents and additives which require numerous physical and chemical treatment methods that tolerate a wide range of pollutants. The application of adsorption treatment for textile wastewater has been studied for years. However, there is very limited data available on the development of eco-friendly composite adsorbent derived from the coconut shell activated carbon (CSAC) and limestone powder (LP) as the core materials and sea-weed algae as the core binder. An attempt was made to determine the effect of sequential treatments of individual adsorbent specifically for the removal of COD, color and Cu(II) from the cotton dyeing wastewater. From the single stage adsorption procedure, CSAC dosage of 8 g/L. was able to remove 49%, 45% and 31% of the COD, color and Cu(II), respectively. Meanwhile, a 6 g/L of LP was found optimum to remove more than 34% of the same parameters. The results also revealed that in order to obtain the spherical bead of adsorbent, 1 to 3% (w/v) of sea-weed algae was required. Furthermore, increasing the molarity of calcium crosslinks led to better beads formation in the range of 3 - 5 mm.